A monoclonal antibody based enzyme-linked immunosorbent assay for detection of phenylethanolamine A in tissue of swine. (15th January 2015) - Li, Yansong; Lu, Shiying; Liu, Zengshan; Sun, Lihui; Guo, Junfei; Hu, Pan; Zhang, Junhui; Zhang, Yuanyuan; Wang, Yang; Ren, Honglin; Meng, Xingyu; Zhou, Yu
Highlights: A McAb specific for PEA was produced. An ELISA based on the McAb for PEA detection tissue of swine was developed. The average recovery of PEA from spiked samples was 103.4%. Abstract: Phenylethanolamine A (PEA) is a phenethanolamine member of the family of β-adrenergic agonists compounds illegally used as feed additives for growth promotion. In this study, PEA was covalently linked to carrier protein cationized bovine serum albumin (cBSA) and egg albumin (OVA). A monoclonal antibody specific for PEA was produced and characteristics of monoclonal antibody (McAb) were studied. Based on the McAb, an enzyme-linked immunosorbent assay (ELISA) for detection of PEA was developed, which showed an IC50 value of 6.25 ng mL −1 and a detection limit of 0.19 ng mL −1 . The average recovery of PEA from spiked samples was 103.4%, which demonstrated that the matrices of meat where PEA may be found do not interfere with the assay.